PENGARUH KOMBINASI SODIUM LAURIL SULFAT DAN NATRIUM KLORIDA TERHADAP KARAKTERISTIK SAMPO EKSTRAK LIDAH BUAYA - Andriani, Luh Nela; Putra, I Gusti NAWW; Tunas, I Ketut (Jurnal Riset Kefarmasian Indonesia, 2022)
The shampoo industry in Indonesia is growing. The shampoo formulation contains 2 main ingredients, namely sodium lauryl sulfate (SLS) and sodium chloride (NaCl). One example of natural ingredients in the manufacture of shampoo is Aloe Vera (Aloe vera L.). This study aims to determine the effect of variations in the concentration of SLS and NaCl on the physical and chemical properties of shampoo. This research is an experimental study with 8 formulas. Includes organoleptic test, homogeneity test, viscosity test, foam height test, specific gravity test, and pH test. Making shampoo preparations by weighing all ingredients according to each formulation, leaving the shampoo for 1 day before testing for 4 weeks of storage.The results showed that the organoleptic test and the homogeneity test of NaCl and SLS had no effect on shampoo. In the specific gravity test and the pH test of NaCl and SLS there was no dominant influence on the specific gravity of shampoo. In the foam height test, the SLS coefficient value is higher than NaCl so that SLS dominantly affects the height of the shampoo foam. In the viscosity test the coefficient value of NaCl is higher than SLS so that NaCl dominantly affects the viscosity of the shampoo. The conclusion from this research is that NaCl has a dominant influence on the physical properties, namely viscosity, while SLS has a dominant influence on the physical properties, namely the height of the shampoo foam.